2010
DOI: 10.1111/j.1398-9995.2010.02399.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variations in the prevalence of atopic sensitization in six study sites across Canada

Abstract: There was a significant variation in atopic sensitization among different study sites across Canada. The prevalence of atopic sensitization is relatively high in Canada compared with sites in the ECRHS and this may, in part, account for the high prevalence of asthma and asthma symptoms in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 24 publications
4
34
1
1
Order By: Relevance
“…These findings seem to be in contrast with the results of a recent observational study from Canada, where it was found that ragweed sensitization was lower in the predominantly rural areas than in urban Canadian cities [31]. There may be various methodological reasons for the differences between this particular study and our findings; it examined healthy adults, whereas we included only patients with suspected or documented atopic diseases.…”
Section: Discussioncontrasting
confidence: 54%
“…These findings seem to be in contrast with the results of a recent observational study from Canada, where it was found that ragweed sensitization was lower in the predominantly rural areas than in urban Canadian cities [31]. There may be various methodological reasons for the differences between this particular study and our findings; it examined healthy adults, whereas we included only patients with suspected or documented atopic diseases.…”
Section: Discussioncontrasting
confidence: 54%
“…Although many large epidemiological studies have reported substantial geographical variation in the prevalence of sensitization, 7, 32, 33 the overall prevalence of allergic sensitization did not vary regionally in NHANES 2005–2006, except in early life. In population-based studies, atopy is often assessed using test panels limited to inhalant allergens, 32, 33 whereas in NHANES 2005–2006, the panel consisted of a variety of indoor, outdoor and food allergens.…”
Section: Discussionmentioning
confidence: 80%
“…Although only 2-3% of individuals in the general population develop allergic sensitization to A. fumigatus (as determined by immediate skin test positivity) 42, 43 , in asthma, approximately 28% of patients including 45% of patients with severe asthma, develop A. fumigatus sensitization 9, 44 . The high rate of sensitization to A. fumigatus in severe chronic asthma may be due to the germination in the lungs of the spores, and exposure and sensitization to the hyphae, which contain the asperamide B lipid.…”
Section: Discussionmentioning
confidence: 99%